Dimensi Etis Terhadap Budaya Makan dan Dampaknya pada Masyarakat - Budianto, V. Irmayanti Meliono (Makara Human Behavior Studies in Asia, 2004)
This research described that the ethical dimensions (food ethics) of the food’s pattern of human beings is coming from their lifes. So, the food’s pattern of human beings was also built and constructed from their culture with many social culture changes, for example, life style, bio-technology, symbolic expression, and ideologies. The results shows that the eating habitat has ethical dimensions about “the good“ and “the bad” in the processing and the marketing of food and making issues of the consumer society by implication.